analysis of Fixed Asset Management at the Regional Financial Board (BKD) of Tanah Datar district - Nurhaliza, Nurhaliza; Amran, Elsa Fitri (UIN MAHMUD YUNUS BATUSANGKAR, 2023)
Fixed assets are tangible assets that have a useful life of more than 12 (twelve) months to be used in government activities or utilized by the general Regional asset management is part of regional financial management covering all activities covering needs planning and budgeting, procurement, use, utilization, security and maintenance, appraisal, transfer, destruction, write-off, administration, and development, supervision and control. The management of fixed assets at the Regional Financial Board (BKD) of Tanah Datar Regency needs to be carried out properly and optimally in order to achieve good fixed asset management. The Tanah Datar Regency Regional Financial Board has several obstacles in carrying out administration, namely in carrying out capital expenditures related to fixed assets because in that year the Tanah Datar Regency Regional Financial Board did not record the time the capital expenditure process occurred. The purpose of this study was to find out whether the management of fixed assets is in accordance with Permendagri No.19 of 2016 at the Regional Financial Board (BKD) of Tanah Datar Regency. The type of research that the researchers did was field research with a qualitative approach. The data sources that researchers use are primary data sources and secondary data sources. Data collection techniques used are interviews and documentation. The results of the research conducted by the author can be concluded that the management of fixed assets carried out by the Regional Finance Agency (BKD) of Tanah Datar Regency as a whole has been carried out properly and is in accordance with Permendagri No.19 of 2016.Keywords: Asset, Fixed Asset, Management